3, 4-Dihydroisocoumarin derivatives from the marine-derived fungus Paraconiothyrium sporulosum YK-03. (June 2017) - Zhang, Li-Hua; Li, Sheng-Ge; Wu, Hong-Hua; Chen, Gang; Li, Li; Bai, Jiao; Hua, Hui-Ming; Wang, Hai-Feng; Pei, Yue-Hu
Graphical abstract: Highlights: Two new 3, 4-dihydroisocoumarin derivatives was isolated from the marine-derived fungus Paraconiothyrium sporulosum YK-03. This is the first report of compounds3 –8 from this fungus. The absolute configuration of compound1 was determined by computational electronic circular dichroism (ECD) method. Abstract: Two new 3, 4-dihydroisocoumarin derivatives, (3 S, 4 S )-4, 5-dihydroxymellein (1 ) and R -(−)-mellein-8- O - β -d -glucopyranoside (2 ), together with six known analogs (3 –8 ) were isolated from the marine-derived fungus Paraconiothyrium sporulosum YK-03. Their structures including absolute configurations were elucidated by extensive spectroscopic methods in combination with computational electronic circular dichroism (ECD) method, optical rotation analysis and monosaccharide composition analysis using HPLC with optical rotation detector. All of them were evaluated for their cytotoxic activities against the human cancer cell lines A549 and MCF-7.